MANAJEMEN CEDERA OLAHRAGA ATLET PEKAN OLAHRAGA PROVINSI IPSI KOTA PONTIANAK TAHUN 2018 - Yuliani, Sherly Devilla; Wati, Isti Dwi Puspita; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to determine the types, causes, treatment and care of injuries that occur during training and martial arts matches. This research is a qualitative mixed study. The method used by the survey. The research sample was the martial arts athletes who competed in the 2018 Pontianak City PORPROV. There were 15 athletes. Data collection techniques in this study were using questionnaires and interviews.Data analysis using descriptive percentages. The results of this study indicate that the type of injury during training, competition is bruising injury on average score of 45% of respondents, 55% of matches, The main cause during training and martial arts matches that often occur is due to collisions as many as 93%, the first handling of injuries during training and competition the respondents said that the most ordered byusing the heat method was 46.67%, the care of injury to the training and the competition was sorted by 53%, 100% of the treatments and treatments were less than optimal (still sick). From these results it was concluded that the injury that often occurs is bruising due to the cause of the collision. Handling and maintenance carried out in order using the heat method.Keybpard: Care, Causes, Treatment, Types.